The quality of life after trans oral video-assisted thyroidectomy and cervical thyroidectomy: a systematic review and meta-analysis - Altedlawi Albalawi, Ibrahim A.; Mirghani, Hyder Osman (Frontiers in Surgery, 2023)
Trans Oral Video-Assisted Thyroidectomy (TOVAT) is increasingly performed for cosmetic reasons. The quality of life after thyroidectomy is important for decision-making. This is the first meta-analysis to compare the quality of life among conventional transcervical thyroidectomies. This meta-analysis aimed to assess the same in the current literature. The authors systematically searched PubMed, Google Scholar, and EBSCO for relevant articles from the first published to December 4, 2022. The keywords endoscopic transoral via vestibular thyroidectomy, transcervical thyroidectomy, conventional thyroidectomy, scarless thyroidectomy, and quality of life were used. Out of the 482 studies retrieved, 27 full texts were reviewed, and only six fulfilled the inclusion and exclusion criteria. Patients with transoral thyroidectomy showed better quality of life that their counterparts who underwent transcervical thyroidectomy at 4-6 weeks following surgery, odd ratio, 2.26, 95% CI, 2.02-2.5, P-value <0.001. Substantial heterogeneity was observed, I2 for heterogeneity, 100%. The quality of life was better among patients who underwent the Trans Oral Video-Assisted Thyroidectomy (TOVAT) compared to their counterparts with the conventional cervical approach (surgical questionnaire). All the components of the SF-36 quality of life questionnaire were better among TOVAT compared to the conventional approach except for social and general health components, which were equal between the two arms. Further multi-center studies with larger samples and controlling for pain and the surgical curve are needed.